Jornalismo automotivo de revista: uma análise multiplataforma - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This monograph discusses magazine automotive journalism, considered a niche of this profession. From this specialization of news production, print magazines play the role of mass media vehicles trying to adapt to the molds of the most modern generations of digital journalism. To do so, they expand their presence to other platforms, such as digital social media, for example. With the intention of being present in other spaces and increasing their audience, magazines end up developing their content from print versions on their websites, replicating the same data to digital mobile media, often without the necessary adaptation to those platforms. This paper aims to compare the multiplatform distribution strategies of these Brazilian automotive magazines. Thus, in the methodology, the Autoesporte, Carro, Motor Show and Quatro Rodas magazines were first selected for an exploratory analysis. After the initial observation, the Autoesporte and Quatro Rodas magazines were selected for a systematic observation analysis of their multiplatform content in some of its fragments, be it in the print magazine, the magazine's representation on the web and three digital social media: Facebook, Instagram and Twitter. Thus, it is identified that these journals go through processes such as the transposition of contents, the hybrid and the reuse of these contents developed on multiple platforms.
Keywords: Periódicos; Jornalismo automotivo; Mídia digital; Journals; Automotive journalism; CNPQ::CIENCIAS SOCIAIS APLICADAS